Настільний теніс як засіб розвитку психофізичних якостей дітей молодшого шкільного віку - Кушнір, Василь Васильович; Kushnir, Vasily (Східноєвропейський національний університет імені Лесі Українки, 2015)
У роботі здійснено теоретичне обґрунтування необхідності розвитку психофізичних якостей у дітей молодшого шкільного віку. Аналіз сучасного стану організації фізичної культури в загальноосвітніх навчальних закладах указує на необхідність модернізації змісту ланки освіти молодших школярів, яка виступає підґрунтям для формування гармонійно розвиненої дитини. Для визначення ефективності чинних програм навчання й виховання проведено педагогічне спостереження дітей молодшого шкільного віку (6–10 років). За його результатами сформульовано проблематику наукового пошуку. Визначено засоби розвитку психофізичних якостей у молодших школярів. Розвиток швидкості, координації та гнучкості лежить у призмі вдосконалення психофізичних складників засобами, що найбільше відповідають віковій категорії молодших школярів. У представленому теоретичному базисі розглянуто можливість використання настільного тенісу в програмі з фізичної культури дітей 6–7 років. Цей час є сенситивним щодо розвитку низки фізичних якостей, закладаються основи культури соматичного й когнітивного здоров’я. Можливість упровадження засобів настільного тенісу є доцільною, науково обґрунтованою та практично спрямованою. The work is devoted to theoretical justification of the need for the development of psycho-physical qualities of children of primary school age. Analysis of the current state of the organization of physical training in secondary educational institutions points to the need to modernize the content of education level of younger students, which is the basis for the formation of a harmonious development of the child. The results.To determine the effectiveness of existing training and education programs were conducted pedagogical supervision of children of primary school age (6–10 years). According to the results of scientific research problems are formulated. Identified by means of psychophysical qualities of the younger students. Development of speed, coordination and flexibility lies in the improvement of mental and physical components of the means most appropriate age category younger students. In the present the theoretical basis of examining the use of table tennis in the program on physical training of children of 6–7 years. This is a sensitive period for the development of a number of physical characteristics, the foundations of culture of somatic and cognitive health. The ability to implement means of table tennis is appropriate, science-based and practical orientation constant. Findings. Most studies on tennis, aimed at sports higher achievements. Younger students are willing to accept and treat with interest innovations on table tennis. Subtle perception when performing tasks tennis 6–7 year old kids will better differentiate the efforts that positively influence the feeling of pen during writing, focus on ball – increase attention and improve vision, explored new motor action – improves memory skills.
Ways of Development of Psycho-physical Qualities of Children of Primary School Age
Keywords: фізична культура; психофізичні якості; молодший шкільний вік; physical education; psychophysical quality; primary school age